(3Odjdc Gdi GdHhQUI hGdGSJKeGQ hGdCSge hCShGb GdeGd (B/s - (3MeOi, MSfs ((3GdbGgQI(B: s (3OGQ GdcJGH GdYQHj(B, s, 2006)
(3jVe ebOeI YGeI aj GdHhQUI hCShGb GdeGd, GOhGJ GdGSJKeGQ(B: (3GdGSge, GdSfOGJ, UfGOjb GdGSJKeGQ, GdChQGb GdeGdjI GdeVehfI HCUhdf TgGOGJ GdGjOGY GdOhdjI, bhGYO GdJYGed aj GdHhQUI(B: (3WQjbI bjO GdTQcGJ aj GdHhQUI hGdbhGYO GdMGceI dYedYG, TQcGJ GdSeSQI hGdbhGYO GdMGceI dYedgG, GdbhGYO GdeJYdbI HaV GdefGRYGJ aj GdHhQUI, fUGFM hJhLjgGJ(B: (3GdGaYGd GdbOQI, GSJKeGQ Ce eZGeQI, GQTGOGJ YGeI, fUGFM GdNHQGA hGdeJNUUjf, eUWdMGJ hJYQjaGJ, SDGd eMjQfjs
(3HHdjhZQGajG(B: (3U(B.249s
Keywords: (3GdGSJKeGQs; (3GdCSges; (3GdHhQUGJs